2022
DOI: 10.1021/acsnano.2c02459
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Then Eliminating Twin Domains in SnSe Thin Films Using Fast Optical Metrology and Molecular Beam Epitaxy

Abstract: van der Waals (vdW) layered chalcogenides have strongly direction-dependent (i.e., anisotropic) properties that make them interesting for photonic and optoelectronic applications. Orthorhombic tin selenide (α-SnSe) is a triaxial vdW material with strong optical anisotropy within layer planes, which has motivated studies of optical phase and domain switching. As with every vdW material, controlling the orientation of crystal domains during growth is key to reliably making wafer-scale, high-quality thin films, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…(d) The SnSe 7 coordination polyhedron. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(d) The SnSe 7 coordination polyhedron. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Discussionmentioning
confidence: 99%
“…(e–h) Demonstrations of structure and phase control through epitaxy: (e) eliminating twin domains. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chin et al 187 used individual elemental source materials to study the self-limiting stoichiometry in SnSe and revealed that within a limited range, changing the Se:Sn flux ratio does not influence the film stoichiometry, but only rotates the primary crystallographic orientation from (210) to (200). By replacing MgO(001) substrates with a-plane sapphire substrates, which have rectangular lattice-matched symmetry that breaks the SnSe domain degeneracy, Mortelmans et al 188 realized SnSe films free of 90°twin defects.…”
Section: Synthesismentioning
confidence: 99%
“…Chang et al used high-purity SnSe granule source materials to grow highly oriented SnSe single layers on graphene substrates using a two-step growth and anneal process. SnSe nanoplates have been produced by optimizing the growth and annealing temperatures. ,, Maintaining stoichiometry is critical for the growth of SnSe. Chin et al used individual elemental source materials to study the self-limiting stoichiometry in SnSe and revealed that within a limited range, changing the Se:Sn flux ratio does not influence the film stoichiometry, but only rotates the primary crystallographic orientation from (210) to (200).…”
Section: Sn Monochalcogenidesmentioning
confidence: 99%